The Effectiveness of the Management of the Modern Tax Administration System at the Soppeng Regency Samsat Office - Nur Asmi; Sirajuddin Saleh; Nasaruddin Hasyim (Journal of Social Science and Economics (JOSSE), 2025)
The purpose of this study is to evaluate how well the Soppeng Regency Samsat Office manages its contemporary tax administration system. Because this research is qualitative, data collection methods that include observation, interviews, recordings and documentation can be used to achieve research objectives. Based on the results of this study, it shows that the effectiveness of the management of the modern tax administration system at the Soppeng Regency Samsat Office can be seen from the indicators of organizational restructuring, technology improvement, improvement of human resource management, and the implementation of good governance has been "effective in managing modern tax administration". It can be seen from the aspect of organizational restructuring, namely the process of significantly restructuring the governance structure which is carried out to get improvements in terms of performance such as increasing efficiency and cutting costs to achieve goals. From the aspect of improving modern administrative management technology, it can be seen from the process of improving or improving existing technology, with the aim of improving work efficiency or functionality. From the aspect of improving HR management, namely the process of improving the development of policy practices and systems used to manage the workforce in an organization, human resources will take part in several trainings in work such as community service, administration and data management. From the aspect of implementing good governance, it can be seen from the use of good governance principles in government offices or organizations that focus on the values of openness, responsibility, efficacy, and efficiency, as well as equality.